A Retroprospective Clinicopathological Study of Prostatic Lesions in Surgical Specimens - Garalla, Hanan M.; Darraz, Khaled M. Ahmed; ESSA, Maggdi M.A. (Libyan International Medical University Journal, 2022)
Background Prostatic diseases such as inflammation, benign prostatic hyperplasia, and tumors are prime causes of mortality and morbidity in males. The prevalence of these lesions increases with advancing age. The second most common cancer among males is prostate cancer, next to lung cancer worldwide.Aim The present study was undertaken with the aim of studying the clinicopathological characteristics of prostate lesions in surgical specimensMethods The present study was a retroprospective study. A total of 212 prostate surgical specimens were included. Information provided in the requisition form regarding age, type of prostatic biopsy and clinical presentation, and histopathological diagnosis was taken into consideration and recorded. All specimens were fixed in 10% neutral buffered formalin and 5μ sections were stained with hematoxylin and eosin stain (H&E stain). Relevant clinical data including age, the presenting complaints, and S.PSA values were recorded. Data were collected and analyzed using simple statistical methods with Microsoft Excel 2016.Results Out of 212 cases analyzed, 161 (76%) were transurethral resection of prostate (TURP) TUPR specimens, 38 (18%) were trucut needle biopsies, and 13 (6%) were open prostatectomy specimens. The youngest patient was 48 years old while the oldest patient was 90 years old with a mean of 71.7  ± 8.2 years. Of the total 212 surgical specimens, 174 (82%) cases were of benign prostatic hyperplasia (BHP), and 38 (18%) were prostatic adenocarcinoma (PAC). Also, 94 (44.3%) of BPH and carcinoma of the prostate cases were most common in the seventh decade of life (61-70 years). Difficulty in micturition was the most common presentation 82 (39%). A maximum number of the BPH cases 81 (46.5%) had the prostate-specific antigen range of 0 to 4 ng/mL. The highest value of serum PSA was noted among the PAC patients in the range of > 80 ng/mL. Out of 38 cases of prostatic adenocarcinoma, moderately differentiated (Gleason scores 7) was the most common core and was seen in 42.1% of the PAC cases.Conclusion The present study showed that the most frequently encountered prostatic lesion was BHP, commonly seen in the age group of 61 to 70 years. The PAC was common among males of more than 60 years. Histopathological examination is the best diagnostic tool for PAC
Keywords: prostate; nodular hyperplasia; adenocarcinoma; TURP; Gleason score